The Urgence of Regulation of Environmental Aesthetic Standards and Security of Administration in The Spatial Detail Plan - Zico Junius Fernando; Wiwit Pratiwi; Rangga Jayanuarto; Muhammad Yusuf Akbar (Institut Agama Islam Negeri (IAIN) Curup, 2021)
Billboards have a considerable influence on urban life because the advertising media often has a location orientation on the main urban roads which has advantages such as strategic location, easy access, agglomeration of activities, completeness of social and economic facilities/facilities, as well as the readiness of the infrastructure. due to the desire to stand out so that the information conveyed is more effective. Advertisements with all their visual characteristics have a major contribution to the impression of an environment. For this reason, it is necessary to arrange advertisements. The arrangement needs to be based on an understanding of the potential and limitations of nature, the development of existing socio-economic activities, as well as the demands of current livelihood needs and environmental sustainability in the future